Mendeley Reference Management Training in Writing Scientific Papers - Bobby Sefrinando; Salahuddin Salahuddin; Edi Rozal Rozal; Hasirah Hasirah; Aris Munandar; Fadli Habibi; Khoirul Anwar (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Mendeley reference management training in writing scientific papers through Community Service (PKM) activities aims to train students of the Islamic Banking study program, Islamic Economics Law study program, and Islamic Economics study program STIE Syari'ah Al-Mujaddid Tanjung Jabung Timur to use Mendeley in writing their scientific papers so that in accordance with the ethics of writing scientific papers. This service involves all students of semester VII (Seven) who are required to make scientific work as a final project to hold a bachelor's degree. This activity is carried out using the method of observation, lectures, and practice, as well as evaluation. The results of this activity are that participants gain knowledge about how to write automatic citations and bibliography on scientific papers according to the APA style 7 format, participants also acquire skills on how to open an account and operate Mendeley Microsoft office word software both based on Mendeley desktop and Mendeley web.